Evolution of nickel hyperaccumulation and serpentine adaptation in the Alyssum serpyllifolium species complex - Sobczyk, M; Smith, J; Pollard, A; Filatov, D (Nature Publishing Group, 2016)
Metal hyperaccumulation is an uncommon but highly distinctive adaptation found in certain plants that can grow on metalliferous soils. Here we review what is known about evolution of metal hyperaccumulation in plants and describe a population-genetic analysis of the Alyssum serpyllifolium (Brassicaceae) species complex, which includes populations of nickel-hyperaccumulating as well as non-accumulating plants growing on serpentine (S) and non-serpentine (NS) soils, respectively. To test whether the S and NS populations belong to the same or separate closely related species, we analysed genetic variation within and between four S and four NS populations from across the Iberian peninsula. Based on microsatellites, genetic variation was similar in S and NS populations (average Ho = 0.48). The populations were significantly differentiated from each other (overall FST = 0.23), and the degree of differentiation between S and NS populations was similar to that within these two groups. However, high S versus NS differentiation was observed in DNA polymorphism of two genes putatively involved in adaptation to serpentine environments, IREG1 and NRAMP4, while no such differentiation was found in a gene (ASIL1) not expected to play a specific role in ecological adaptation in A. serpyllifolium. These results indicate that S and NS populations belong to the same species and that nickel hyperaccumulation in A. serpyllifolium appears to represent a case of adaptation to growth on serpentine soils. Further functional and evolutionary genetic work in this system has the potential to significantly advance our understanding of the evolution of metal hyperaccumulation in plants.